The diagnostic importance of the bronchoalveolar lavage in lymphocytic alveolitis. Issue 1 (2nd January 2017) - Mlika, Mona; Kria, Nourane; Braham, Emna; Chebbi, Chokri; El Mezni, Faouzi
ABSTRACT: Multidisciplinary concertation is mandatory in order to assess interstitial pneumonias. The study of the bronchoalveolar lavage helps evoking a diagnosis according to the lavage profile. In lymphocytic alveolitis, immunocytochemistry, or in flux cytometry are necessary in order to identify the different clusters of lymphocytes implicated. Our objective was to evaluate the profile of 31 lymphocytic alveolitis using 2 different techniques which are the immunocytochemistry and the in flow cytometry in order to evaluate the efficacy of each technique and to compare the different results to the final diagnoses. We describe a retrospective study about 31 patients admitted to our hospital in order to explore an interstitial pneumonia between January and July 2014. Bronchial endoscopy and bronchoalveolar lavage were performed in all cases. The sensitivity of the in flow cytometry was estimated to 53% and its specificity reached 33%. On the other hand, the immunocytochemistry presented a specificity of 42.8% and a sensitivity of 42.8%. The final diagnoses retained consisted in sarcoidosis in 12 cases, infectious pneumonia in 10 cases, hypersensitivity pneumonia in 3 cases, cryptogenic pneumonia in 3 cases, idiopathic fibrosis in 2 cases, and adenocarcinoma in 1 case. The relevance of both techniques depends on many factors. They necessitate an available material, well-trained technicians, and experimented pathologists.